Tropical forests and adaptation to climate change: in search of synergies - Robledo, C.; Kanninen, M.; Pedroni, L. (Center for International Forestry Research, 2005)
This book encompasses inputs from science, policy making and development cooperation with regard to the linkages between climate change, sustainable livelihoods and biological diversity. It presents experiences, challenges and alternatives to scientists and practitioners for commonly assessing the needs of poor livelihoods to successfully cope with climate change as well as for bridging the gap towards a meaningful implementation of adaptation measures. It is based on the recognition of the need to establish a bridge between science, policy making and development cooperation with regard to promoting adaptation to climate change and variability at the local level. Many of the articles included are based on the discussions that took place during the international workshop on “Adaptation to Climate Change, Sustainable Livelihoods and Biological Diversity“, held March 2004 in Turrialba, Costa Rica.